SURVIVAL ANALYSIS OF THE FIRST JOB WAITING TIME FOR GRADUATES USING THE COX PROPORTIONAL HAZARD MODEL BASED ON THE MAXIMUM LIKELIHOOD ESTIMATION PRINCIPLE: SURVIVAL ANALYSIS OF THE FIRST JOB WAITING TIME FOR GRADUATES USING THE COX PROPORTIONAL HAZARD MODEL BASED ON THE MAXIMUM LIKELIHOOD ESTIMATION PRINCIPLE - Dhea Urfina Zulkifli; Riaman; Kankan Parmikanti; Bambang Ruswandi (Fraction: Jurnal Teori dan Terapan Matematika, 2022)
Every university graduate certainly expects to obtain the desired job as soon as possible. But in reality, because of high competitiveness in job markets many graduates have long waiting time to get a job. Survival analysis can be used to analyse the length of waiting time to obtain the first job. Thus, the objectives of this research are to get Cox Proportional Hazard model parameter on the length of waiting time of the graduate of Faculty of Social and Political Sciences Syarif Hidayatullah State Islamic University Jakarta to obtain the first job based on Maximum Likelihood Estimation principle and to explain factors influencing the graduate’s length of waiting time to obtain the first job by analysing the variable of gender, GPA, and study program. Data used in this research are from document of the faculty. The research found Cox Proportional Hazard model parameter on the graduate’s length of waiting time to obtain the first job and its significant influential factors, namely GPA and study program.